Single-cell RNA sequencing reveals the effects of mental stress on mouse mammary tumors and the tumor microenvironment - Pengfei Liu; Wenjing Ma; Tao Wang; Jinhui Lü; Weizhong Wang; Yixing Wang; Qifan Tang; Jing Di; Evelyne Bischof; Qian Zhao; Zuoren Yu (Cell Death Discovery)
Abstract Mental stress has been shown to negatively impact the development and progression of human cancer, including breast cancer. However, its effects on the tumor microenvironment (TME) remain unclear. In this study, we applied single-cell sequencing analysis to tumor tissues from MMTV-PyMT transgenic mice with mammary gland tumors with or without exposure to mental stress. In association with a significant promotion of the cell cycle and tumor growth induced by mental stress, we observed the dedifferentiation of luminal subtype of tumor cells into a subgroup of cancer stem cell-like basal cells, as well as enhanced cell proliferation in epithelial tumor cells, endothelial cells, and fibroblasts. In addition, stress stimulation led to an increase in tumor-associated neutrophils (TANs) and tumor-infiltrating dendritic cells (TIDCs), while suppressing immune cells such as cytotoxic T lymphocytes (CTLs), naïve T cells, B cells, and NK cells within the TME. We also observed a shift in macrophages from the M1 to the M2 phenotype. Furthermore, pathway enrichment analysis of differentially expressed genes, gene signature U score analysis, and immunofluorescence staining of the tumor tissue sections were conducted for further validation. The current study not only systematically elucidates the impact of mental stress on mammary gland tumors and the TME in vivo, but also provides insights into the mechanism underlying mental stress-induced tumor growth and progression in breast cancer.